Pengaruh Gaya Kepemimpinan Demokratis Kepala Madrasah dan Kompetensi Guru terhadap Kinerja Guru di MTs Persatuan Umat Islam (PUI) Kota Bogor - Amie Primarni; Imam Tholkhah; Kurniasih Kurniasih (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Teacher performance will be optimal when it is integrated with components per school, whether it is the principal, teachers, employees or students. Some of the indicators used as the basis for assessing the low quality of education in the country can be considered, including the low competence of teaching staff, the direction and policy of education itself, and various problems directly related to teaching staff. The purpose of this study was to determine the influence of the madrasa principal's democratic leadership style on teacher performance, the influence of teacher competence on teacher performance, and the effect of democratic leadership style and teacher competence simultaneously on teacher performance at MTs Persatuan Umat Islam (PUI) Bogor City. This research is a quantitative study using the survey method, data analysis using statistical tests, simple and multiple linear regression tests with the help of the SPSS Version 26.0 for windows program. The research population is all 23 teachers at the Islamic Community Association MTs (PUI) Bogor City for the 2022 academic year. /2023 The sample was taken by saturated sampling, namely all teachers in the study population were 23 teachers. Data collection techniques using a questionnaire. The results of the research show that there are three conclusions. First, there is no significant effect of the democratic leadership style of the madrasa principal (X1) partially on teacher performance (Y) with a value of Sig. = 0.353 > 0.05 and tcount <ttable (0.949 <2.086), r square (R2) of 0.041 or 4.1% and the linear regression equation Ŷ = 78.585 + 0.130 X1 2. Both have a significant influence on teacher competency (X2) partially on teacher performance (Y) with a Sig. = 0.000 <0.05 and tcount > ttable (5.716 > 2.086) of 0.609 or 60.9% and the linear regression equation Ŷ = 35.792 + 0.242X2. Third, there is the influence of the democratic leadership style of the madrasa head (X1) and teacher competency (X2) simultaneously on teacher performance (Y) with a Sig. = 0.000 <0.05 and the value of Fcount > Ftable (23.597 > 3.467) of 0.702 or 70.2% and the linear regression equation Ŷ = 45.358 - 0.241)X1 + 0.309X2.